The Relationship Between the Skeletal Age and the Chronological Age Among Patients Attending Dental Clinic of Faculty of Dentistry, USIM - Diana Md Zahid; Azrul Hafiz Abdul Aziz; Zahid, Salmi Md (American Scientific Publishers, 2024)
Indexed by Scopus